Paradoxical reactions in Buruli ulcer after initiation of antibiotic therapy: Relationship to bacterial load - Frimpong, Michael; Agbavor, Bernadette; Duah, Mabel Sarpong; Loglo, Aloysius; Sarpong, Francisca N.; Boakye-Appiah, Justice; Abass, Kabiru M.; Dongyele, Mathias; Amofa, George; Tuah, Wilson; Frempong, Margaret; Amoako, Yaw A.; et al. (PLOS Neglected Tropical Diseases, 2019)
Background We investigated the relationship between bacterial load in Buruli ulcer (BU) lesions and the development of paradoxical reaction following initiation of antibiotic treatment. Methods This was a longitudinal study involving BU patients from June 2013 to June 2017. Fine needle aspirates (FNA) and swab samples were obtained to establish the diagnosis of BU by PCR. Additional samples were obtained at baseline, during and after treatment (if the lesion had not healed) for microscopy, culture and combined 16S rRNA reverse transcriptase/ IS2404 qPCR assay. Patients were followed up at regular intervals until complete healing. Results Forty-seven of 354 patients (13%) with PCR confirmed BU had a PR, occurring between 2 and 42 (median 6) weeks after treatment initiation. The bacterial load, the proportion of patients with positive M. ulcerans culture (15/34 (44%) vs 29/119 (24%), p = 0.025) and the proportion with positive microscopy results (19/31 (61%) vs 28/90 (31%), p = 0.003) before initiation of treatment were significantly higher in the PR compared to the no PR group. Plaques (OR 5.12; 95% CI 2.26–11.61; p<0.001), oedematous (OR 4.23; 95% CI 1.43–12.5; p = 0.009) and category II lesions (OR 2.26; 95% CI 1.14–4.48; p = 0.02) were strongly associated with the occurrence of PR. The median time to complete healing (28 vs 13 weeks, p <0.001) was significantly longer in the PR group. Conclusions Buruli ulcer patients who develop PR are characterized by high bacterial load in lesion samples taken at baseline and a higher rate of positive M. ulcerans culture. Occurrence of a PR was associated with delayed healing. Trial registration ClinicalTrials.gov NCT02153034.